Profile of brivaracetam and its potential in the treatment of epilepsy - Ferlazzo E (Dove Medical Press, 2015)
Edoardo Ferlazzo,1,2 Emilio Russo,3 Laura Mumoli,1 Chiara Sueri,2 Sara Gasparini,1,2 Caterina Palleria,3 Angelo Labate,1 Antonio Gambardella,1 Giovambattista De Sarro,3 Umberto Aguglia1,2 1Department of Medical and Surgical Sciences, Magna Græcia University, Catanzaro, 2Regional Epilepsy Centre, Bianchi-Melacrino-Morelli Hospital, Reggio Calabria, 3Institute of Pharmacology, Magna Græcia University, Catanzaro, Italy Abstract: Brivaracetam (BRV) (UCB 34714) is currently under review by the US Food and Drug Administration and European Medicines Agency for approval as an add-on treatment for adult patients with partial seizures. Similar to levetiracetam (LEV), BRV acts as a high-affinity ligand of the synaptic vesicle protein 2A, however, it has been shown to be 10- to 30-fold more potent than LEV. Moreover, BRV does not share the LEV inhibitory activity on the high voltage Ca2+ channels and AMPA receptors, and it has been reported to act as a partial antagonist on neuronal voltage-gated sodium channels. The pharmacokinetic profile of BRV is favorable and linear, and it undergoes an extensive metabolism into inactive compounds, mainly through the hydrolysis of its acetamide group. Furthermore, it does not significantly interact with other antiepileptic drugs and more than 95% is excreted through the urine, with an unchanged fraction of 8%–11%. BRV has a half-life of approximately 8–9 hours and it is usually given twice daily. To date, a wide range of experimental studies have reported the effectiveness of BRV with regards to partial and generalized seizures. In humans, six randomized, placebo-controlled trials and two meta-analyses highlighted the efficacy, or good tolerability, of BRV as an add-on treatment for patients with uncontrolled partial seizures. A wide dose range of BRV has been evaluated in those trials (5–200 mg), but the most suitable for clinical use appears to be 50–100 mg/day. The most common adverse reactions to BRV are mild to moderate, transient, often improve during the course of the treatment, and mainly consist of central nervous system symptoms, such as fatigue, dizziness, and somnolence. The aim of this paper is to critically review the literature data regarding experimental animal models and clinical trials on BRV, and to define its potential usefulness for the clinicians who manage patients with epilepsy. Keywords: seizures, animal, therapy, drug, antiepileptic